Practical and facile approach towards indole alkaloids: (-)-mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, Rasapalli; Kalkote, Uttam R. (Synlett, 2007)
An efficient approach to (-)-mitralactonine using Pictet-Spengler cyclisation with a highly functionalised masked aldehyde is described. Sharpless asymmetric dihydroxylation (SAD) is utilised to introduce chirality in the key substrate.
Keywords: alkaloids; asymmetric; cyclisations; dihydroxylations; thioacetats